Islamic and Science Study of Jombang “Kenduren” Culture in Learning Materials - Shofia Maghfiroh; Feby Permata Sari; Mirsya Adelia (Proceeding International Conference on Religion, Science and Education, 2023)
The purpose of this study was to analyze the integration of science material and Islamic religious education in the Jombang "Kenduren" tradition. Kenduren is a community tradition that is held once a year to commemorate gratitude for garden produce. At the "kenduren" event, the community distributes the number of durians in accordance with the year of implementation. This research method is a qualitative research in Wonosalam Village, Jombang Regency, East Java Province. Data collection was carried out through observational studies and literature studies. The results of the analysis state that in the "Kenduren" tradition there is integration between Islamic religious education and science. Islamic studies contained in this tradition are a form of gratitude and sharing activities among the people of Wonosalam village. This shows the implementation of habluminallah and habluminannas in people's lives. While the study of science in the "Kenduren" tradition can be linked to the concepts of physics, chemistry, and biology. The preparation of kenduren applies the concepts of physics to the theory of balance, parabolic motion, and energy; chemical concepts in the theory of biomolecules; as well as biological concepts in the theory of biodiversity and natural ecosystems.